A COMPARATIVE ASSESSMENT OF PHARMACOLOGICALLY ACTIVE PRINCIPLES AND ANTIOXIDANT ACTIVITY OF COMMONLY OCCURRING MUCUNA SPS. IN INDIA - Soma Narasimha, Murthy; Malgaonkar, Manasi M.; Shirolkar, A. R.; Pawar, S. D.; Sangvikar, S.; Kulkarni, Y.R. (International Journal of Ayurveda and Pharma Research, 2015)
The genus Mucuna (Fabaceae) includes about 150 species and almost all the species are reported to contain L-3,4-dihydroxy phenylalanine (L-Dopa), a non-protein amino acid that acts as precursor for the neurotransmitter dopamine, used in the treatment of Parkinsons disease. The present study was aimed to assess the pharmacologically active principles and antioxidant activities of Mucuna pruriens (L.) DC., Mucuna bracteata DC., Mucuna cochinchinensis (Lour.) A. Chev. black seeds sp. and Mucuna cochinchinensis (Lour.) A. Chev. white seeds sp. The aqueous extract of plant material was subjected to assess the pharmacologically active principles by using L-dopa quantification, determination of protein and flavonoids, total phenolic content, Inhibition of DPPH radical and Reducing power/Ferric reducing antioxidant potential (FRAP) assays. The results obtained showed that, Mucuna cochinchinensis black seeds sp. has highest protein, total phenolic content, L-dopa content and DPPH radical scavenging activity. Mucuna bracteata seeds showed highest flavonoid content whereas, in FRAP assay Mucuna pruriens extract showed highest potential to reduce the ferric ions. It can be concluded from this study that, L-DOPA possesses antioxidant activity which was supported by in-vitro antioxidant assays. This indicates that the antioxidant activity of the aqueous extracts of all the Mucuna sps. may be due to the presence of L-Dopa content in its seed.